COMPARISON OF COLORING INTENSITY OF COTTON FABRIC WITH RICE FIELD CLAY AND CLIFF CLAY - Mayang Yulasna; Agusti Efi (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2024)
The use of natural clay materials as textile coloring as an effort to restore the use of environmentally friendly natural dyes and abandon the use of synthetic dyes that are dangerous because they can pollute the environment and have an impact on humans in textile coloring. This study aims to describe the coloring results of natural coloring, namely rice field liek soil and cliff liek soil, as well as the color intensity/dark light color produced using tunjung mordant on the results of cotton fabric coloring with different soaking times. The approach used is an experiment with a data collection technique using a questionnaire from 15 panelists, for the results of color intensity/dark light color (Value), the resulting color is not significant at a significance level of 0.439> 0.05. This means that there is no significant difference due to the type of clay used in soaking cotton materials with rice field liek soil and cliff liek soil.